2023
DOI: 10.3389/fmicb.2023.1101111
|View full text |Cite
|
Sign up to set email alerts
|

Integrative ATAC-seq and RNA-seq analyses of IPEC-J2 cells reveals porcine transcription and chromatin accessibility changes associated with Escherichia coli F18ac inhibited by Lactobacillus reuteri

Abstract: Escherichia coli is the main cause of postweaning diarrhea in pigs, leading to economic loss. As a probiotic, Lactobacillus reuteri has been used to inhibit E. coli in clinical applications; however, its integrative interactions with hosts remain unclear, especially in pigs. Here, we found that L. reuteri effectively inhibited E. coli F18ac adhering to porcine IPEC-J2 cells, and explored the genome-wide transcription and chromatin accessibility landscapes of IPEC-J2 cells by RNA-seq and ATAC-seq. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…All these RCT studies are depicted in Table 2. Enterotoxigenic E. coli is a main pathogen of infectious diarrhea in childhood and postweaning piglets (Kotloff, 2022;Qin et al, 2023b). Gut microbiota disruption observed in diarrheal piglets was described as a reduction of Lactobacillus, enriched abundance of E. coli, and increased lipopolysaccharide (LPS) biosynthesis (Li et al, 2023b).…”
Section: Diarrheamentioning
confidence: 99%
See 1 more Smart Citation
“…All these RCT studies are depicted in Table 2. Enterotoxigenic E. coli is a main pathogen of infectious diarrhea in childhood and postweaning piglets (Kotloff, 2022;Qin et al, 2023b). Gut microbiota disruption observed in diarrheal piglets was described as a reduction of Lactobacillus, enriched abundance of E. coli, and increased lipopolysaccharide (LPS) biosynthesis (Li et al, 2023b).…”
Section: Diarrheamentioning
confidence: 99%
“…Walsham et al reported that L. reuteri can bind to the epithelial cell surface by mucus-binding proteins CmbA and MUB, thus inhibiting enteropathogenic E. coli adherence to the gut epithelium (Walsham et al, 2016). Bioinformatics analysis further revealed that the inhibition mechanism may be associated with PI3K-Akt and MAPK signaling pathways (Qin et al, 2023b). Furthermore, L. reuteri may inhibit harmful bacteria by the production of antimicrobial metabolites like reuterin (Asare et al, 2020).…”
Section: Remodeling the Gut Microbiotamentioning
confidence: 99%
“…Firstly, ATAC-seq eliminates the need to precisely control the amount of enzyme required for DNase-seq and the need to determine the duration of formaldehyde crosslinking for FAIRE-seq [14]. Second, ATAC-seq requires only a small sample size of 500 to 50,000 cells for library preparation and takes only three hours, as opposed to the two techniques that require two to three days, making it much simpler and faster [15]. Thirdly, ATAC-seq provides higher resolution and sensitivity for the detection of open chromatin regions, allowing the identification of smaller regulatory elements such as enhancers and transcri`ption factor binding sites [16].…”
Section: Introductionmentioning
confidence: 99%